2014
DOI: 10.1038/nchembio.1608
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new ATP-binding motif involved in peptidic azoline biosynthesis

Abstract: Despite intensive research, the cyclodehydratase responsible for azoline biogenesis in thiazole/oxazole-modified microcin (TOMM) natural products remains enigmatic. The collaboration of two proteins, C and D, is required for cyclodehydration. The C protein is homologous to E1 ubiquitin-activating enzymes, while the D protein is within the YcaO superfamily. Recent studies have demonstrated that TOMM YcaOs phosphorylate amide carbonyl oxygens to facilitate azoline formation. Here we report the X-ray crystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(172 citation statements)
references
References 55 publications
10
159
0
Order By: Relevance
“…For example, Babinger, Sterner and colleagues used SSNs to survey sequence/function space in the geranylgeranylglyceryl phosphate synthase family and identified previously unrecognized subfamilies that differ in substrate specificities from members that had been biochemically and structurally characterized [13]. Mitchell, Nair, and coworkers used SSNs to analyze sequence/function space in the YcaO superfamily of ATP-binding proteins involved in the synthesis of heterocyclic natural products [14]. van der Donk, Nair, and colleagues used SSNs to explore functional relationships among the glutaminylation domains of lantibiotic dehydratases [15].…”
Section: Sequence Similarity Network (Ssns)mentioning
confidence: 99%
“…For example, Babinger, Sterner and colleagues used SSNs to survey sequence/function space in the geranylgeranylglyceryl phosphate synthase family and identified previously unrecognized subfamilies that differ in substrate specificities from members that had been biochemically and structurally characterized [13]. Mitchell, Nair, and coworkers used SSNs to analyze sequence/function space in the YcaO superfamily of ATP-binding proteins involved in the synthesis of heterocyclic natural products [14]. van der Donk, Nair, and colleagues used SSNs to explore functional relationships among the glutaminylation domains of lantibiotic dehydratases [15].…”
Section: Sequence Similarity Network (Ssns)mentioning
confidence: 99%
“…Azol(in)e formation in TOMM systems involves the recently characterized ATP-binding YcaO family (90, 91), but neither MbnB nor MbnC bears any similarity to those enzymes, and both lack nucleotide-binding motifs. Thioamide biosynthesis is less well understood, but a YcaO family enzyme has been proposed to be responsible for thioamide biosynthesis in thioviridamide as well (88).…”
Section: Methanobactinsmentioning
confidence: 99%
“…1,2 Previous research has demonstrated that the TOMM D domain catalyzes the ATP-dependent cyclodehydration reaction, while the TOMM C domain recognizes the peptide substrate through specific motifs within the N-terminal leader peptide and regulates D domain activity. 3–5 However, the biophysical basis for leader peptide binding and activity potentiation by the C domain has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%